2014
DOI: 10.7314/apjcp.2014.15.19.8499
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Risk Factors in Women Participating in a Breast Screening Program: a Study on 11,850 Iranian Females

Abstract: The incidence rate of breast cancer in developed countries is almost three-fold higher than in developing countries. Iran has had one of the lowest incidence rates for breast cancer in the world, but during the recent decades a marked increase has been seen. The purpose of this study was to investigate some

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 29 publications
6
20
0
Order By: Relevance
“…Further, 19.09% had low BMI (less than 18.5) indicating underweight. Similar findings were also observed by Sepandi M et al [20] and Meshram II et al [19] in different studies [19,20].…”
Section: Discussionsupporting
confidence: 80%
“…Further, 19.09% had low BMI (less than 18.5) indicating underweight. Similar findings were also observed by Sepandi M et al [20] and Meshram II et al [19] in different studies [19,20].…”
Section: Discussionsupporting
confidence: 80%
“…In 18 articles, the data of age at menarche were reported in terms of age groups (qualitatively) (18,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Three articles had similar data (24)(25)(26) and therefore only one of them was included in the analysis.…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…Therefore, the results of the present study were heterogeneous and the difference among studies or Tau 2 = 0.18. From 7 analyzed studies, 3 studies showed no significant relation between obesity and breast cancer (8,17,18). Out of 7 analyzed studies, 5 studies reported no significant relation between overweightness and breast cancer in women (8,17,18,21,23).…”
Section: Effect Of Exposurementioning
confidence: 99%
“…In one article (8), overweightness was the protecting factor and 4 studies showed no significant relation between overweightness and breast cancer (17,18,21,23).…”
Section: Effect Of Exposurementioning
confidence: 99%